2015
DOI: 10.1016/j.jiph.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial synergy studies of carbapenem-resistant Acinetobacter baumannii isolated from intensive care units of a tertiary care hospital in Egypt

Abstract: The increasing prevalence of multidrug-resistant and pan drug-resistant Acinetobacter baumannii as a cause of nosocomial infections has led to the need for the reassessment of novel combinations of antibiotics as our only current viable option for handling such infections until a new therapeutic option becomes available. Two of the most commonly used methods for testing antimicrobial synergy are the Time-kill assay method and the E-test method, and these were the methods used in this study. Antibiotic combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, the effects of drug ratio in the spray drying feed solution on the surface coating and aerosolisation are unknown. In this study, colistin was co-spray-dried with a hydrophobic antibiotic, azithromycin, at various mass ratios as such combination has shown synergy in antimicrobial effects (22, 23). Surface coating coverage by azithromycin on particle surfaces was characterised by two surface analytical techniques, X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of drug ratio in the spray drying feed solution on the surface coating and aerosolisation are unknown. In this study, colistin was co-spray-dried with a hydrophobic antibiotic, azithromycin, at various mass ratios as such combination has shown synergy in antimicrobial effects (22, 23). Surface coating coverage by azithromycin on particle surfaces was characterised by two surface analytical techniques, X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS).…”
Section: Introductionmentioning
confidence: 99%
“…Author concluded that azithromycin and polymyxin B combination is justifiable and advised. It may be converted into convenient curative strategy by synergism between two or more drugs results in lowering the effective MIC values with addition to their pharmacological and biological effects to determine the actual therapeutic dosage of these antimicrobial in combinations for clinical practice [19]. Manikal et al interrogated synergism method i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to the suggestions by Odds ( 32 ), sitafloxacin and sulbactam exhibited no interaction in 84% of XDR- A. baumannii strains included in the present study. The time-kill assay was performed to further investigate the bactericidal activity of the two drugs and their combination ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%